A novel approach to synthesize micrometer-sized porous silicon as a high performance anode for lithium-ion batteries. (August 2018) - Jia, Haiping; Zheng, Jianming; Song, Junhua; Luo, Langli; Yi, Ran; Estevez, Luis; Zhao, Wengao; Patel, Rajankumar; Li, Xiaolin; Zhang, Ji-Guang
Abstract: Porous structured silicon (p-Si) has been recognized as one of the most promising anodes for Li-ion batteries. However, many available methods to synthesize p-Si are difficult to scale up due to their high production cost. Here we introduce a new approach to obtain spherical micrometer-sized silicon with unique porous structure by using a microemulsion of the cost-effective of silica nanoparticles and magnesiothermic reduction method. The spherical micron-sized p-Si particles prepared by this approach consist of highly aligned nano-sized silicon and exhibit a tap density close to that of bulk Si particles. They have demonstrated significantly improved electrochemical stability compared to nano-Si. Well controlled void space and a highly graphitic carbon coating on the p-Si particles enable good stability of the structure and low overall resistance, thus resulting in a Si-based anode with high capacity ( 1467 mAh g −1 at 2.6 A g −1 ), enhanced cycle life (370 cycles with 83% capacity retention), and high rate capability ( 650 mAh g −1 at 11A g −1 ). This approach may also be generalized to prepare other hierarchical structured high capacity anode materials for constructing high energy density lithium ion batteries. Graphical abstract: The table of contents entry: Microsphere silicon with unique structure can be prepared by a novel approach starting from SiO2 nanoparticles. The obtained micro-sized silicon exhibits a tap density close to that of bulk Si particles. Well controlled void space and a highly graphitic carbon coating on the designed silicon particles enable good stability of the structure and low overall resistance, thus resulting in a Si-based anode with high capacity, enhanced cycling performance and high rate capability. fx1 Highlights: Microsphere silicon with unique structure can be prepared by a novel approach starting from cost-effective SiO2 nanoparticles. The obtained microsphere silicon demonstrates high tap density, which is close to that of bulk Si particles. 2, 3-dihydroxynaphthalene (DN) as carbon source can provide highly graphitic carbon which can futhur improve the electrochemical performance of silicon. The preserved void space and the high quality of carbon coating enable the micro-Si good stability of the structure and promising performance.